Factors contributing to school dropout among the girls: a review of literature - Karim, A.H.M Zehadul; Shahidul, S. M. (Progressive Academic Publishing, 2015)
Though a lot of research have been concerned with school dropout issue for both girls and boys, dropout pattern significantly differs by the gender of the students. This paper clarifies the factors that contribute to the increasing dropout rate of children, particularly among girls by making a detailed review of available literature. Most past reviews on the school dropout issue have been carried out regardless of the gender of the students. A few of the studies in this context have been done on girls' dropout outcome based on particular regions and cultures of the world. In this paper, we identify the factors and illustrate a conceptual model for girls' dropout from school. We demonstrate that though some factors can cause an increase in the dropout rate regardless of the gender of students, these factors mainly contribute to an increase in the dropout rate particularly for female students. In our conceptual model we try to illustrate how a range of particular factors can affect students' educational outcome which consequently produce dropout among girls in schools in general. And finally, we provide a few recommendations which policy planners may adopt in reducing girls' dropout from schools.